Cyclic behavior of sandy shoals on the ebb-tidal deltas of the Wadden Sea. (1st March 2016) - Ridderinkhof, W.; Hoekstra, P.; van der Vegt, M.; de Swart, H.E.
Abstract: Ebb-tidal deltas are bulges of sand that are located seaward of tidal inlets. Many of these deltas feature shoals that cyclically form and migrate towards the coast. The average period between successive shoals that attach to the coast varies among different inlets. In this study, a quantitative assessment of the cyclic behavior of shoals on the ebb-tidal deltas of the Wadden Sea is presented. Analysis of bathymetric data and Landsat satellite images revealed that at the majority of inlets along the Wadden Sea migrating shoals occur. The average period between succeeding shoals correlates to the tidal prism and has values ranging between 4 and 130 years. A larger tidal prism favors larger periods between successive shoal attachments. However, such a relationship was not found for wide inlets with multiple channels. There is a positive relationship between the frequency with which the shoals attach to the coast and their migration velocity, and a negative relationship between the migration velocity of the shoal and the tidal prism. Finally, the data were too sparse to assess whether the longshore sediment transport has a significant effect on the period between successive shoals that attach to the coasts downdrift of the observed tidal inlets. Abstract : Highlights: Migrating shoals are found on all ebb-tidal deltas of the West and East Frisian Wadden inlets. There is a clear difference between the behavior of migrating shoals on ebb-tidal deltas seaward of inlets that are comprised of either a single or multiple channels. For inlets that are comprised of a single channel the following relationships are found: A larger tidal prism correlates with (1) a longer period between successive shoals, and (2) a lower migration velocity.